Analisis tingkat kepuasan pelanggan terhadap kualitas pelayanan di mall x dengan metode Customer Satisfaction Index (CSI) (Studi kasus: PT. XYZ) - Sari, Puspita; Zamzani, Muhamad Imron (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes customer satisfaction in a mall by involving 100 respondents selected using Slovin's formula with a 10% margin of error. Data were collected through questionnaires that had been tested for validity and reliability, where the calculated r-value was greater than the critical r-value (0.195) and Cronbach's Alpha exceeded 0.60. Customer satisfaction was analyzed using the Customer Satisfaction Index (CSI), calculated by dividing the weighted average by the maximum scale (5). The results showed a CSI score of 78.96%, which falls into the